Consonant and Vowel Processing in Word Form Segmentation: An Infant ERP Study - Von Holzen, Katie (Brain Sci, 2018)
Segmentation skill and the preferential processing of consonants (C-bias) develop during the second half of the first year of life and it has been proposed that these facilitate language acquisition. We used Event-related brain potentials (ERPs) to investigate the neural bases of early word form segmentation, and of the early processing of onset consonants, medial vowels, and coda consonants, exploring how differences in these early skills might be related to later language outcomes. Our results with French-learning eight-month-old infants primarily support previous studies that found that the word familiarity effect in segmentation is developing from a positive to a negative polarity at this age. Although as a group infants exhibited an anterior-localized negative effect, inspection of individual results revealed that a majority of infants showed a negative-going response (Negative Responders), while a minority showed a positive-going response (Positive Responders). Furthermore, all infants demonstrated sensitivity to onset consonant mispronunciations, while Negative Responders demonstrated a lack of sensitivity to vowel mispronunciations, a developmental pattern similar to previous literature. Responses to coda consonant mispronunciations revealed neither sensitivity nor lack of sensitivity. We found that infants showing a more mature, negative response to newly segmented words compared to control words (evaluating segmentation skill) and mispronunciations (evaluating phonological processing) at test also had greater growth in word production over the second year of life than infants showing a more positive response. These results establish a relationship between early segmentation skills and phonological processing (not modulated by the type of mispronunciation) and later lexical skills.